Leveraging Advanced Electrical Engineering Technologies for Offshore Construction Support: A Conceptual Overview - Ojong Felix Enow; Ebimor Yinka Gbabo; Andrew Tochukwu Ofoedu; Possible Emeka Chima; Oluwapelumi Joseph Adebowale (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Offshore construction presents unique challenges that demand innovative solutions to ensure project success and operational efficiency. This conceptual overview explores the transformative potential of advanced electrical engineering technologies in optimizing offshore construction support processes. The abstract highlights the integration of smart grid solutions, automation, control systems, and communication infrastructure to address key challenges faced in offshore projects. Traditional offshore construction methods often encounter limitations in power distribution, control systems, and communication networks, leading to inefficiencies and increased operational risks. However, recent advancements in electrical engineering offer promising opportunities for overcoming these challenges. This paper examines the role of advanced electrical engineering in enhancing power distribution and management through smart grid solutions and the integration of renewable energy sources. Additionally, it explores the implementation of automation and control systems, including robotics and AI-driven predictive maintenance, to streamline construction and maintenance tasks offshore. Furthermore, the paper discusses the importance of robust communication infrastructure, such as high-speed data transmission and cybersecurity measures, for real-time monitoring and control of offshore assets.Through case studies and examples, this overview showcases successful deployments of advanced electrical engineering technologies in recent offshore projects, emphasizing their impact on project outcomes and cost-effectiveness. Looking ahead, the paper offers insights into future developments and emerging trends in offshore construction support, highlighting the potential for collaboration and knowledge sharing among industry stakeholders.In conclusion, this conceptual overview underscores the critical role of advanced electrical engineering technologies in revolutionizing offshore construction support, paving the way for sustainable and efficient offshore energy production and infrastructure development.